A Tale of Freshwater Scarcity: Water Resources of Namibia - Coetzee, Marina E. (Journal of Central European Green Innovation, 2023)
This article introduces the various water resources available to Namibia, an arid country in southern Africa. With low and extremely variable annual rainfall and high evaporation rates, surface water is scarce. Permanent rivers are only found along the southern and northern borders. Ephemeral rivers flow for short periods after thundershowers and few reach the ocean. Many ephemeral rivers sink into the gravelly and sandy riverbeds, where they feed alluvial aquifers. Groundwater is the only water source for about 80% of the territory. Dams were built in ephemeral rivers to create artificial lakes that play an important role in water provision for urban areas, irrigation schemes and mines. Despite the extreme aridity, Namibia has a variety of wetland habitats, including five Ramsar sites.
Keywords: Namibia; water resources; freshwater scarcity; dams; groundwater